MODERN TRENDS IN THE DEVELOPMENT OF THE TECHNOLOGIES FOR PRODUCTION OF DENTAL CONSTRUCTIONS. - Tsanka Dikova; Dzhendo Dzhendov; Maksim Simov; Iveta Katreva-Bozukova; Svetlana Angelova; Diana Pavlova; Metodi Abadzhiev; Tsvetan Tonchev (Peytchinski Publishing, 2015)
The aim of the present paper is to make a review of the modern trends in the development of the technologies for production of dental constructions. Three are the main trends in production technologies in dentistry last 30 years: digitalization, simulation and implementation of additive technologies. The simulation occurred first and due to the computers development it underwent fast progress from the mathematical calculations and analytical analysis to the 3D modeling and visualization. Thus Computer Aided Engineering (CAE) was developed, allowing dental constructions with optimal design to be produced by optimal technological regimes. The first Computer Aided Design (CAD) - Computer Aided Manufacturing (CAM) systems were created in 1970s as a result of the digitalization. In this mode of operation at first virtual 3D model is generated by CAD, which then is used for production of the real construction by CAM. The CAD-CAM systems allow fabrication of dental restorations which is difficult or impossible to be manufactured by conventional technologies. The development of CAD unit runs from indirect scanning of the plaster model for obtaining data for the 3D model to direct scanning of the prosthesis area. While the development of CAM unit leads to direct manufacturing of the real dental construction using subtractive or additive technologies. The future development of the CAD-CAM systems as a whole characterizes with transition from closed to open access systems, which make them more flexible. In the late 1980sthe new approach to the production of constructions appeared - by addition of material layer by layer. The additive technologies were developed. They characterize with building of one layer at a time from a powder or liquid that is bonded by means of melting, fusing or polymerization. Stereo lithography, fused deposition modeling, selective electron beam melting, laser powder forming and inkjet printing are the methods, mostly used in dentistry. Due to the great variety of the additive manufacturing processes various materials can be used for production of different dental constructions for application in many fields of dentistry. The simulation, digitalization and implementation of additive technologies in dentistry led to fast development of the technologies for production of dental constructions last decade. As a result many of manual operations were eliminated, the constructions' accuracy increased and the production time and costs decreased.